Benford's law in the Beale ciphers. Issue 3 (13th May 2021) - Wase, Viktor
Abstract: The Beale Papers is an 1885 pamphlet in which there are three ciphers, said to contain the location of a hidden treasure. In this paper the ciphers are viewed through Benford's Law. Statistical analysis show that the the ciphers deviate from the law—cipher 2 less so than 1 & 3. Furthermore the numbers in the uncracked ciphers do not come from the same distribution as the cracked one, but it seems that the uncracked ciphers might share a similar random distribution. One possible explanation is that cipher 1 & 3 are faked in a similar manner, another is that they might share the same key.